Digital repositories: one concept, multiple visions - D'Alí²s-Moner, Adela (Anuario ThinkEPI, 2010)
Data on the growth of the "digital universe" are presented and a global vision of how different organizations -companies, governments, archives, libraries and museums- approach and manage digital content. Key issues to be considered for proper management of digital repositories are proposed.